A Multiresolution Model for the Simulation of Transient Heat and Mass Transfer - Alam, Jahrul M.; Kevlahan, Nicholas K.-R.; Vasilyev, Oleg V.; Hossain, Zahangir (Taylor & Francis, 2012)
The development of an efficient computational methodology for transient heat and mass transfer applications is challenging. When a solution is localized on the fraction of a com- putational domain, an appropriate adaptive mesh method could minimize computational work. In this article, we propose a novel adaptive-mesh multiresolution algorithm for the transient momentum and energy equations. The nonlinear dynamics between the velocity and temperature fields are modeled by solving the coupled system of equations simul- taneously, where the rate of convergence has been optimized so that computational cost remains proportional to the number of grid points. Numerical experiments have exhibited good agreements with benchmark simulation data.
Keywords: mult-scale mode; heat transfer; wavelets